The Symbolic Meaning of the Wireng Dance Choreography at the Kasunanan Surakarta Palace - Jazuli, Muhammad; Suharji, Suharji; Pebrianti, Sestri Indah (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2022)
The aim of this research is to find out the specifications of the choreographic form and the symbolic meaning of wirèng in the Kasunanan Palace. A qualitative descriptive research design with form-matching techniques was employed; meanwhile, the data collection techniques employed observation, interviews, and literature study. The data analysis includes the form of the wirèng choreography and its symbolic meaning. From the results of the study, it was found that the choreographic form of wirèng in Kasunanan was used for pair dances and had a soldier’s theme, while in Mangkunagaran wirèng was used to denote the term dance because wirèng is synonymous with the word beksan which means dance. The pattern of the wirèng choreography in Kasunanan has specifications, namely: (1) it is performed by male and female dancers in an even number, (2) it consists of three parts, namely the initial part (maju beksan), the main part (beksan), and the final part (mundur beksan), (3) in the main part of the dance there are variations of the dance scenes and variations of war scenes, such as madras wars or gending wars, referring to a typical war dance which is accompanied by slow (lamba) and constant (steady) rhythmic gendhing or music, and ruket wars which are accompanied by fast-rhythmic pieces of music (mipil-lancaran), (4) changes and differences always follow every change of part in the composition of the accompaniment pieces. Wirèng’s symbolic meaning reflects the value system prevailing in the palace environment, symbolized by the numbers zero, two, and three, movement characteristics, and movement patterns (gawang) in the choreography.